Root estimation in Galton–Watson trees. Issue 3 (7th January 2022) - Brandenberger, Anna M.; Devroye, Luc; Goh, Marcel K.
Abstract: Given only the free‐tree structure of a tree, the root estimation problem asks if one can guess which of the free tree's nodes is the root of the original tree. We determine the maximum‐likelihood estimator for the root of a free tree when the underlying tree is a size‐conditioned Galton–Watson tree and calculate its probability of being correct.